2015
DOI: 10.1002/hup.2470
|View full text |Cite
|
Sign up to set email alerts
|

Influence of depression and anxiety on circulating endothelial progenitor cells in patients with acute coronary syndromes

Abstract: The current study indicates that EPCs circulate in decreased numbers in ACS patients with depression or anxiety and, therefore, contribute to explore new perspectives in the pathophysiology of the association between cardiovascular disorders and affective disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…Several studies have reported elevated concentrations of CRP in MDD even after controlling for potential confounders, such as cigarette smoking [43]. Recent data showed a reduced number of endothelial progenitor cells, a marker of ED, in patients with MDD acute coronary syndrome [44]. Circulating oxidative stress markers have also been found among patients with MDD [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported elevated concentrations of CRP in MDD even after controlling for potential confounders, such as cigarette smoking [43]. Recent data showed a reduced number of endothelial progenitor cells, a marker of ED, in patients with MDD acute coronary syndrome [44]. Circulating oxidative stress markers have also been found among patients with MDD [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with anxiety have impaired flow-mediated dilation of the vasculature, which suggests greater endothelial dysfunction [66-69]. Patients with GAD, PD, and obsessive compulsive disorder have decreased levels of circulating endothelial progenitor cells that are vital to healthy endothelial function and prevent progression of CAD [70]. Furthermore, patients with PTSD鈥攅specially those with active symptoms鈥攈ave increased levels of soluble tissue factor and von Willebrand Factor, two substances that are secreted by endothelial cells and have been implicated in inflammation, thrombosis, and ultimately the development of atherosclerosis [71].…”
Section: Mechanisms Mediating the Relationships Between Anxiety Disormentioning
confidence: 99%
“… 15 , 16 , 17 In this regard, there is recent evidence on reduced levels of circulating EPCs in patients with depression and acute coronary syndromes. 18 , 19 Oxidative stress, measured by circulating markers (superoxide dismutase, glutathione, oxLDL, among others) in plasma and platelets, 10 vascular relaxation 20 and animal models, 21 , 22 has been closely associated with major depression. 23 , 24 Studies in a depression model with chronic mild stress rats demonstrated associations between endothelial dysfunction, oxidative stress and depression-like symptoms that were modulated by chronic SSRI.…”
Section: Introductionmentioning
confidence: 99%